POLITIK HUKUM PEMBENTUKAN KANTOR STAF PRESIDEN BERDASARKAN PERATURAN PRESIDEN NOMOR 26 TAHUN 2015 TENTANG KANTOR STAF PRESIDEN - Reni Lestari; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Presidential Staff Office is formed through Presidential Regulation Number 26 of 2015concerning the Presidential Staff Office. Whereas in the presidential environment there are three institutionsthat function as supporting the performance of the President, namely,The Presidential Staff Office is , StateSecretariat and Secretariat Cabinet. Juridically, the authority of these institutions overlaps each otherbecause their functions are both as assistants to the President. So, it is necessary to review the legal politicsofThe Presidential Staff Office formation. Based on this understanding, the writing of this thesis formulatestwo problem formulations, namely: First, how is the legal politics of the establishment of the PresidentialStaff Office based on Presidential Regulation Number 26 of 2015 concerning the Office of the PresidentialStaff ?. Second, is there a clash of authority between the Presidential Staff Office both internally in thepresidential institution and in the external presidential institution ?.The research method in this study, first, the type of research is normative law and descriptiveanalysis. Second, data sources, supported by primary data sources, secondary data sources and tertiarydata sources. Third, the data collection technique used is the Literature Study. After the data collected isthen analyzed qualitatively, then draw conclusions with deductive thinking methods. From the results ofproblem research there are two main things that can be concluded, first, Political law in the formationofThe Presidential Staff Office is intended as an institution that guarantees the implementation ofgovernment programs as stated in nawacita. Secondly, judicially, The Presidential Staff Office authorityoverlaps with Setkab and Setneg as institutions supporting the President's performance. The suggestion ofthe author, first, is that it is necessary to control the institutions that have overlapping authority.Keywords: Presidential Institution - Office of Presidential Staff - Overlapping Authority